The Nutritional Quality Potential of Microgreens, Baby Leaves, and Adult Lettuce: An Underexploited Nutraceutical Source - Martínez-Ispizua, Eva; Calatayud, Ángeles; Marsal, José I.; Cannata, Claudio; Basile, Federico; Abdelkhalik, Abdelsattar; Soler, Salvador; Valcárcel, José Vicente; Martínez-Cuenca, Mary-Rus (MDPI, 2022)
Interest in the cultivation of lettuce landraces is increasing because native varieties, as high-quality products, are particularly attractive to consumers. Lettuce is a popular leafy vegetable worldwide, and interest in the consumption of first leaves (microgreens) and seedlings (baby leaves) has grown due to the general belief that young plants offer higher nutritional value. The content of some bioactive compounds and antioxidants (chlorophylls, carotenoids, anthocyanins, ascorbic acid, phenols, antioxidant activity) was monitored in six lettuce landraces and five commercial varieties, and compared across three development stages: microgreen, baby, and adult. Ascorbic acid and phenolic contents were 42% and 79% higher, respectively, in the early stages than in adult lettuces, and red-leaf varieties (CL4 and L11) stood out. This finding agrees with lettuce’s marked antioxidant capacity and correlates with its pigment contents, especially anthocyanins. The nutritional value of adult lettuce is conditioned by its size, shape, and head structure as phytochemical concentrations are regulated by light. The low content of ascorbic acid, phenolics, and anthocyanins in crisphead lettuce (CL5) is a clear example (49, 67%, and 27% lower, respectively, than the adult mean). Our results indicate the wide variability of lettuces’ nutritional characteristics and emphasize that traditional varieties are a helpful source of agricultural biodiversity.